2015
DOI: 10.3389/fmicb.2015.00303
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adhesins in virulence of Paracoccidioides spp.

Abstract: Members of the Paracoccidioides genus are the etiologic agents of paracoccidioidomycosis (PCM). This genus is composed of two species: Paracoccidioides brasiliensis and Paracoccidioides lutzii. The correct molecular taxonomic classification of these fungi has created new opportunities for studying and understanding their relationships with their hosts. Paracoccidioides spp. have features that permit their growth under adverse conditions, enable them to adhere to and invade host tissues and may contribute to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 77 publications
3
38
0
Order By: Relevance
“…brasiliensis uses a sequence of different mechanisms to establish successful infections, beginning with the first contact with host cells and extending through the later stages of disease. 48,49 The reduced initial adhesion observed in this study suggests that the Pb14-3-3 gene products strongly influence the initial adhesion, as reported by Andreotti et al, 2005, 27 Da Silva et al, 2013 28 and De Oliveira et al, 2015, 50 but the requirement for these proteins was bypassed following extended contact with the host cell.…”
Section: Discussionsupporting
confidence: 65%
“…brasiliensis uses a sequence of different mechanisms to establish successful infections, beginning with the first contact with host cells and extending through the later stages of disease. 48,49 The reduced initial adhesion observed in this study suggests that the Pb14-3-3 gene products strongly influence the initial adhesion, as reported by Andreotti et al, 2005, 27 Da Silva et al, 2013 28 and De Oliveira et al, 2015, 50 but the requirement for these proteins was bypassed following extended contact with the host cell.…”
Section: Discussionsupporting
confidence: 65%
“…This type of therapy is known as anti-adhesion therapy and can be an effective way to improve the efficacy of PCM treatments. In support of this idea, de Oliveira et al (2015) demonstrated that when blocking two important Paracoccidioides spp. adhesins, enolase and 14-3-3, using specifics antibodies, host organisms were able to resist fungal infection and showed increased survival.…”
Section: Introductionmentioning
confidence: 84%
“…The pathogen’s ability to colonize and invade the host tissue is strictly dependent on these proteins and the adhesion capacity of the fungus. de Oliveira et al (2015), using in vivo animal models, demonstrated that the ability to express adhesins and adhere to the host are decisive factors in the virulence of different Paracoccidioides spp. isolates.…”
Section: Introductionmentioning
confidence: 99%
“…This adherence mechanism is mediated by molecules, named adhesins, present on the fungal surface that allow it not only to adhere but also to invade the host tissues, contributing to development of the mycosis. Thus, several adhesins have been reported, including the 14–3–3 protein enolase, triose phosphate isomerase (TPI), glyceraldehyde 3‐phosphate dehydrogenase (GAPDH), the glycoprotein Gp43 (the main immunodominant antigen) and a hydrolase (HAD32) (de Oliveira et al ., ; Pereira et al ., ; Barbosa et al ., ; Torres et al ., ; Mendes‐Giannini et al ., ; Hernández et al ., ). Moreover, the 14–3–3 protein and Gp43 induce apoptosis in human pneumocytes (Silva et al ., ).…”
Section: Virulence Factorsmentioning
confidence: 98%